COVID-19 and Work-from-home - Korpič Horvat, Etelka (Anali PAZU HD, 2022)
An employment contract for home working has existed in Slovenian labour legislation for over 50 years, but such contracts had hitherto only rarely been concluded. This shifted overnight with the COVID-19 pandemic. Home working entails that an employee works from home or at some other premises of their own choosing. An employment contract for home working is an atypical labour law contract that allows greater flexibility as regards employment. The author outlines its advantages for employees, employers, and the state. Before the outbreak of the COVID-19 pandemic this type of work was not common, regardless of the fact that in Slovenia information and telecommunications technology enabling teleworking has been widely accessible for many years. Based on the legislation in force, the author presents conditions for such employment and underlines important elements of an employment contract for teleworking. In addition, the author draws attention to certain open questions regarding the principle of equal treatment, payment for work, the right to health and safety at work, the right to social security, etc.